ASSOCIATION OF HEMOGLOBIN LEVELS WITH CLINICAL OUTCOME IN PATIENTS ADMITTED WITH NSTEMI AND STEMI.: http://doi.org/10.46536/jpumhs/2023/13.03.456 - Bushra Aqeel1 , Sharwan Bhuro Mal2 , Shazia Kazi3 , Mirza Rizwan Baig4 , Syed Fasih A. Hashmi5 , Muhammad Zaman Baloch6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
INTRODUCTION: Acute myocardial infarction is the leading cause of death and hospital admissions worldwide. In previously conducted studies, levels of hemoglobin was associated with negative outcome in hospitalized patients. Data is limited in our region in this regard, that is why this study aims to determine association between hemoglobin levels among patients admitted with acute myocardial infarction. MATERIAL AND METHODS: A clinical prospective study was conducted through a convenient sampling technique. The study site was a tertiary care Isra University Hospital. Hyderabad and data was collected from the patients admitted in the department of cardiology. All the patients admitted with acute myocardial infarction AMI, age between 30 years to 70 years, both male and female were selected in inclusion criteria. Hemoglobin Hb was divided into three categorize, i Normal Hb between 12gm/dl to 16gm/dl both in males and females, ii Anemia Hb <12gm/dl, and polycythemia Hb >16gm/dl. In-hospital outcome complications and mortality was assessed and compared with level of hemoglobin using chi-square and student’s t-test, where appropriate. A p value of <0.05 was considered as statistically significant. RESULTS: A total of 128 patients were enrolled for final analysis. Patients with NSTEMI were more prevalent than STEMI, 88 68.75% and 40 31.25%. Most of the patients with acute myocardial infarction AMI had normal hemoglobin levels n = 90, 70.31% while anemia was observed among 26.56% n = 34 of the patients. Anemia was significantly observed in patients with NSTEMI n = 22, 17.18% as compared to patients with STEMI n = 12, 9.37%, 0.001. Mean difference of hemoglobin levels among anemic NSTEMI vs. STEMI was also observed significant, -0.48±0.3 gm/dl, p 0.02. Overall mortality was observed in 5.46% n = 7. In both groups, higher in-hospital mortality was observed in anemic patients with STEMI n = 3, 7.5% as compared to anemic patients with NSTEMI n = 2, 1.56%. CONCLUSION: Our study concludes that patients with STEMI were less anemic than patients admitted with NSTEMI. Rate of complications were observed higher among NSTEMI anemic patients while in-hospital mortality was significantly higher among STEMI anemic patients